1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00810.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Mutagenesis of PH‐20 Hyaluronidase from Human Sperm

Abstract: The cDNA encoding PH-20 hyaluronidase from human sperm has been mutated at five positions by in vitro mutagenesis. We have changed three acidic amino acids and two arginine residues that are conserved in the sequence of mammalian PH-20 polypeptides as well as in the hyaluronidases from bee and hornet venom. Of the former, the mutants [Gln113]PH-20 and [Gln249]PH-20 had no detectable enzymatic activity; the mutant [AsnllllPH-20 had about 3% activity. The mutant [Thr252]PH-20 was also inactive, while [Gly176]PH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 24 publications
7
54
0
2
Order By: Relevance
“…However, major spatial differences were evident in the structure of HYALP1, in particular amino acid moieties that appear to be important for the proper positioning of the substrate with regard to the acidic amino acid moieties within the active centre ( Figure 6B). The active sites of these enzymes consist of aspartate and glutamate residues interspaced by one amino acid residue [45,46]. Notably, HYAL5 and SPAM1, yet also HYALP1, show this particular feature.…”
Section: Discussionmentioning
confidence: 96%
“…However, major spatial differences were evident in the structure of HYALP1, in particular amino acid moieties that appear to be important for the proper positioning of the substrate with regard to the acidic amino acid moieties within the active centre ( Figure 6B). The active sites of these enzymes consist of aspartate and glutamate residues interspaced by one amino acid residue [45,46]. Notably, HYAL5 and SPAM1, yet also HYALP1, show this particular feature.…”
Section: Discussionmentioning
confidence: 96%
“…Its side chain is partially buried, forming a hydrogen bond with Asn229 (located on R5) and a salt bridge with Arg271 (located on R6), both invariant residues in the human hyaluronidases. Replacement of this glutamic acid by a glutamine residue in hPH-20 led to loss of activity (41). The deleterious effect of a mutation in this position is expected to arise from reduced protein stability due to removal of the electrostatic interaction between R5 and R6.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that these 90 bases make up the entire exon 2, and therefore, HYAL1-v1 is generated by splicing of exon 2 (26). It is noteworthy that the 30-amino acid sequence encoded by exon 2 is not a part of the catalytic domain; however, it is well conserved in all six human hyaluronidases and also in the bee hyaluronidase (33)(34)(35)(36). The observation that HYAL1-v1 is enzymatically inactive and that a similar splice variant of HYAL-3 (HYAL3-v1) is also enzymatically inactive may explain why this 30-amino acid sequence that is encoded by a separate exon in both HYAL1 and HYAL3 is well conserved (26).…”
Section: Discussionmentioning
confidence: 99%